(untitled) (mathematica didactica, 2024)
Since working problems is an important part of novice university student’s learning, we qual- itatively analyzed solving processes. Occurring diffi- culties are mainly traced back to a lack of prior knowledge which mostly prohibit serious problem- solving activities. Students were not able to resolve that issue by using lecture notes.